x-(2x-1)=3

Simple and best practice solution for x-(2x-1)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(2x-1)=3 equation:


Simplifying
x + -1(2x + -1) = 3

Reorder the terms:
x + -1(-1 + 2x) = 3
x + (-1 * -1 + 2x * -1) = 3
x + (1 + -2x) = 3

Reorder the terms:
1 + x + -2x = 3

Combine like terms: x + -2x = -1x
1 + -1x = 3

Solving
1 + -1x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + -1x = 3 + -1

Combine like terms: 1 + -1 = 0
0 + -1x = 3 + -1
-1x = 3 + -1

Combine like terms: 3 + -1 = 2
-1x = 2

Divide each side by '-1'.
x = -2

Simplifying
x = -2

See similar equations:

| 4a+8c=16 | | x^2-2.6x-3.12=0 | | 6a+12q=18 | | x/7+x/6=39 | | x-38=24 | | x^2+x-272=0 | | 130=5(x-60)+55 | | -9(-5d-12)-9d=-18d | | 2y+4=3y+12 | | 6(-17g+4)=20-17g+4 | | 3x-24=2x | | 12x=81 | | 64-y=36 | | 7m-3m+1= | | -7=-(x+8) | | V-5=0 | | x/5+x/7=24 | | 3x-6=8x+-4x | | 2(3x+4)-(3x-2)=8 | | 9-4x=5x+9 | | 6x-3=6(x+1) | | 3x+12-5*5=22 | | x/2+x/3=5/6 | | -5x+2+2x=-6x+7 | | 2k-22=8(K+1) | | (15n)+4=36 | | 17.1d=18d+17.19 | | 2n/5-6/13=74/65 | | 8x/9-5=59 | | 4(2x-7)-2=4(x-2)+6 | | .35c+9.99=11.74 | | 6.6h-7.15-16.2h=-6.6h+19.25 |

Equations solver categories